PENCITRAAN PEREMPUAN: PENDEKATAN KULTURAL FEMINIS TERHADAP CERPEN â€LIHUNâ€ KARYA LUXUN - neni Kurniawati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
Â In traditional Chinese culture, patriarchy is a system adopted by its people. This system is based on Confucian school. It then influents values, rules, philosophy, relations and ways of life of traditional Chinese people. In its actual application, woman is subordinate to man.They always oppressed by this system. This paper describes images of power female figure in relation to others, both within the family or society in their culture. By doing close reading, it can be assumedÂ that there are efforts to prosecute her rights as a full human beings. This female character has been oppressed by system, but she has power to take actions by showing her attitude to refuse discriminative treatment from society dominated by patriarchal system. Although at last she Â is not completely successful, but there are efforts based on her own initiative to fight the discrimination and some changes for her rights.Keywords: Lihun, divorce, Chinese culture, feminism, LuxunÂ